DISCURSIVE ‘OTHERING’ OF CHINA IN THE US PRESIDENT DONALD TRUMP’S FOREIGN POLICY (Journal of Contemporary Studies, 2023)
The aim of this paper is to understand the role of identity discourses in US foreign policy towards China. It focuses on the foreign policy of Donald Trump to deconstruct his discourse on China as ‘different’ and, therefore, a ‘threat’ which eventually justified the trade war policies and non-cooperation on the COVID 19 pandemic. There is a continuation of similar identity based, foreign policy ventures under Joe Biden administration. By employing constructivism, it is argued that the relationship between identity and foreign policy is performative; identity is constructed through discourse, which consequently shapes the foreign policy of a state. To understand this relationship of performativity, Donald Trump’s foreign policy towards China is analyzed by applying Lene Hanson’s inter-textual critical discourse analysis model. It unfolds that the American mainstream newspapers constructed the events of trade war and COVID-19 in line with Trump’s ‘China threat’ narrative. This inter-textuality between the official and unofficial discourse legitimized Trump’s otherization of China as a threat and, consequently, his policies.